Post-photostimulation energy intake accelerated pubertal development in broiler breeder pullets - S.H. Hadinia; P.R.O. Carneiro; C.J. Fitzsimmons; G.Y. Bédécarrats; M.J. Zuidhof (Poultry Science, 2020)
The effect of ME intake (MEI) on the reproductive system was evaluated. Ross 308 broiler breeder pullets (n = 140) were assigned to 2 treatments from 22 to 26 wk of age: (1) Low-energy diet fed restricted (2,807 kcal/kg, low MEI) and (2) high-energy diet fed unrestricted (3,109 kcal/kg, high MEI). Daylength was increased from 8 to 14 h at 22 wk of age with a light intensity of 30 lux. Daily palpation was used to detect sexual maturity via the presence of a hard-shelled egg in the shell gland. Expression of gonadotropin releasing hormone-I (GnRH) and gonadotropin inhibitory hormone (GnIH) genes in the hypothalamus and GnRH receptor (GnRH-RI) and GnIH receptor (GnIH-R) genes in the anterior pituitary gland of each pullet was evaluated from 22 to 26 wk of age using quantitative real time-PCR. Blood samples were taken weekly and luteinizing hormone (LH), follicle stimulating-hormone (FSH), and 17-beta-estradiol (E2) determined using commercial ELISA kits. Carcass samples were used for determination of CP and fat content. Data were analyzed using the MIXED procedure in SAS, and differences were reported where P ≤ 0.05. High MEI treatment pullets had 2.3-fold higher GnRH and 1.8-fold higher GnRH-RI mRNA levels than low MEI pullets. MEI affected neither expression of GnIH and GnIH-R nor carcass protein content. For high MEI (489 kcal/D) and low MEI treatments (258 kcal/D), respectively, from 22 to 26 wk of age (P ≤ 0.05), LH concentration was 3.05 and 1.60 ng/mL; FSH concentration was 145 and 89.3 pg/mL; E2 concentration was 429 and 266 pg/mL, and carcass lipid was 13.9 and 10.3%. The onset of lay for pullets in the high MEI treatment advanced such that 100% had laid by 26 wk of age compared with 30% in the low MEI treatment. We concluded that higher MEI advanced the activation of the hypothalamic–pituitary–gonadal axis and also increased body lipid deposition, and moreover, stimulated reproductive hormone levels which overall accelerated puberty in broiler breeder pullets.